Evaluating discrete trial teaching with instructive feedback delivered in a dyad arrangement via telehealth. Issue 4 (11th September 2020) - Ferguson, Julia L.; Majeski, Maddison J.; McEachin, John; Leaf, Ronald; Cihon, Joseph H.; Leaf, Justin B.
Abstract : Telehealth research in the field of applied behavior analysis (ABA) has focused on the training and supervision of others to implement various behavior analytic procedures. Current guidelines for practicing telehealth suggest that direct telehealth services may be appropriate for some individuals diagnosed with autism spectrum disorder, but more research is needed. This study evaluated the effects of discrete trial teaching with instructive feedback in a dyad arrangement delivered directly via telehealth to teach tact relations to 6 children diagnosed with autism spectrum disorder. All participants and the experimenter were located in different physical locations. All participants learned their primary and secondary targets, and 5 of the participants acquired the observational primary and secondary targets without direct teaching. Areas of future research and clinical implications are discussed in the context of telehealth service delivery.